Role of Unilateral Vocal Cord Palsy in Causing Recurrent Tracheobronchial Foreign Bodies - Pincet, Laurence; Lambercy, Karma; Sandu, Kishore (Frontiers in Pediatrics, 2019)
Foreign body (FB) aspiration in children is a frequent condition managed by ENT pediatric surgeons and pediatric pulmonologists. We present the case of a 20-months-old child who presented with three recurrent episodes of FB aspiration. At the time of FB removal, an initial dynamic examination of the larynx revealed a unilateral vocal cord palsy (UVCP). For recurrent tracheobronchial FB inhalation, we recommend a systematic dynamic airway endoscopy.